INFLUENCE OF PERSONAL SELLING, SALES PROMOTION AND CUSTOMER SATISFACTION ON CUSTOMER LOYALTY At PT AMMAY CEMERLANG NUSANTARA, MEDAN - Fransisca Fortunata; Nurmaidah Ginting; Selviany Luhur; Edy Gunawan; Meilisa Sinaga (SEAN Institute, 2023)
The results show that the adjusted r square value is 0.464 which means that 46.4% of customer loyalty demand is jointly influenced by the variables described in the model. While the rest is influenced by factors outside the model. Partially, personal selling variable has a positive and significant effect, sales promotion variable has a positive and significant effect, customer satisfaction variable has a positive and significant effect. Simultaneous, service quality, trust and customer satisfaction have a positive and significant effect.